Development of ‘16-Holes Manual Dexterity Pegboard’ and the Normal Value of 6 Years Old Children - Fanny Aliwarga; Ferial Hadipoetro; Angela BM Tulaar; Surjanto H (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objectives: Obtaining the standard normal value of 6 years old children aged six year, and testing our hypothesis if girls’ dexterity is higher than boys.Methods: The design of this study was a cross sectional study of six years old students of public elementary school in South Jakarta. Inclusion criteria included age six years old, no neurological andorthopedic problem, normal nutritional status and right handed. Location based-random sampling was performed. Dependent variables comprised of age, sex and nutritional status. Independent variable wasthe result of ‘16-Holes Three-Jaw Chuck Manual Dexterity Pegboard’ test. Statistical analysis was done by descriptive analysis and Mann Whitney Test.Results: There were 191 girls and 191 boys who fulfilled the criteria. The ‘16-Holes Three-Jaw Chuck Manual Dexterity Pegboard’ test allowed subjects to be assessed for their ability to put numbers of pegwithin 15 seconds. The mean number of pegs placed for girls was 6.92 pegs (CI 95% 6.76 – 7.08) and boys was 6.49 pegs (CI 95% 6.33 – 6,65)Conclusions: Girls are able to place more pegs than boys in a given time. Furthermore, girls’ manual dexterity is superior to boys (p 0,000).Keywords: Manual dexterity, standard normal value, pegboard, sex differences.